TRANSONIC FLOWS, SHOCK WAVE — TURBULENT BOUNDARY LAYER INTERACTION - PIOTR DOERFFER; JAROSŁAW KACZYŃSKI (TASK Quarterly, 1998)
Shock wave - boundary layer interaction is one of the most important phenomenon in transonic flows. Due to its complexity it is difficult as well for experimental as for numerical study. The growing potential of the CFD is therefore of high importance. Different aspects of shock wave - boundary layer interaction should be studied in different flow configurations. Therefore results concerning profile flow, helicopter rotor at hovering and forward flight and internal flows are presented in this paper. These are to illustrate our ability in CFD in general. Besides the flows simulation the work directed to a development of used codes is carried out.